Nonadherence as four-day antiretroviral therapy interruptions: Do depression and race/ethnicity matter as much in the modern antiretroviral therapy era? - Sauceda, John A. (AIDS Behav, 2016)
HIV+ White, Latino, and African Americans (N = 1,131) completed a survey advertised on social media to re-examine the effect of depressive symptoms (via the Patient Health Questionnaire; PHQ-9) and race/ethnicity on antiretroviral therapy nonadherence (defined as past 3-month, four-day treatment interruption). An adjusted logistic regression showed a 15% increase in odds for a treatment interruption per 1-unit increase on the PHQ-9. The effect of depressive symptoms on nonadherence was greater for Latinos (OR=1.80, p<.05), but not for African Americans, compared to Whites. The benefits of modern ART (e.g., simpler, forgiving to minor lapses) may not circumvent the effect of depressive symptomatology.